2011
DOI: 10.1109/tkde.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

SwiftRule: Mining Comprehensible Classification Rules for Time Series Analysis

Abstract: In this article, we provide a new technique for temporal data mining which is based on classification rules that can easily be understood by human domain experts. Basically, time series are decomposed into short segments, and short-term trends of the time series within the segments (e.g., average, slope, and curvature) are described by means of polynomial models. Then, the classifiers assess short sequences of trends in subsequent segments with their rule premises. The conclusions gradually assign an input to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In [14], [15] we have shown that a 0 , a 1 , a 2 , a 3 , etc. can be interpreted as the optimal estimators of average, slope, curve, change of curve, etc.…”
Section: Novel Features Describing Trends In Time Seriesmentioning
confidence: 98%
See 3 more Smart Citations
“…In [14], [15] we have shown that a 0 , a 1 , a 2 , a 3 , etc. can be interpreted as the optimal estimators of average, slope, curve, change of curve, etc.…”
Section: Novel Features Describing Trends In Time Seriesmentioning
confidence: 98%
“…With a given representation of a time series by orthogonal expansion coefficients, two time series can be compared simply by taking the Euclidian distance (or the scaled Euclidean distance) of two orthogonal expansion coefficient vectors [15]. Doing so, the temporal effort to compare precomputed coefficient vectors is marginal.…”
Section: Novel Features Describing Trends In Time Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem has been researched extensively and has not yet been solved satisfactorily (Abonyi et al 2003;Abonyi et al 2005;Liu et al 2008;Keogh and Kasetty 2003;Fuchs et al 2009Fuchs et al , 2010Fisch et al 2011;Kehagias et al 2005;Seghouane and Amari 2007). Kehagias et al (2005) presented a DP algorithm that uses Schwarz's Bayesian information criterion (BIC) as the segmentation order selection criterion (Seghouane and Amari 2007) to find the globally optimal segmentations for every value of segmentation order.…”
Section: Introductionmentioning
confidence: 99%